Analysis and Outlook for the Development of Measles Epidemic Situation during the COVID-19 Pandemic - T. A. Semenenko; A. V. Nozdracheva (Эпидемиология и вакцинопрофилактика)
Relevance. The success of the global community in the fight against measles through vaccination at the beginning of the twentyfirst century allowed WHO to declare the goal of eliminating this infection by 2010. However, ten years later, the problem of the growing incidence of measles has become relevant again for all countries of the world. The pandemic of the new coronavirus infection (COVID-19) has affected all spheres of human life and has exacerbated the situation in the fight against other infections, including those managed with the help of specific prophylaxis. Since the measles contagiosity index and mortality rate are significantly higher than similar characteristics of COVID-19, the risk of increasing the incidence of this infection in the coming years is difficult to overestimate.Aim of the study: to assess the epidemic situation of measles in the context of the COVID-19 pandemic, as well as the prospects for its development; to propose preventive measures.Materials and methods. The article analyzes the statistical materials available on the official websites of the WHO (WHO). https://www.who.int/data/), the CDC US (https://www. cdc.gov) and the Federal Service of Rospotrebnadzor (https://www.rospotrebnadzor.ru/) on vaccination coverage and measles incidence in 13 countries in the WHO European Region and the United States. The epidemic situation on measles, as well as the level of population coverage with vaccination against its pathogen in the Russian Federation, were assessed according to the Federal State Statistical Observation forms 2010 – 2020: Form 2 «Information on infectious and parasitic diseases» and Form 6 «Information on the populations of children and adults vaccinated against infectious diseases».Results. It has been established that the increase in the measles incidence occurred in 2017–2019 worldwide, including European countries with a population coverage of two vaccine doses at the 97% level between 2010 and 2019. The prevalence of measles cases in children under the age of 10 is shown, as well as the wide range (from 56.9% to 10.9%) in the proportion of vaccinated persons among them. The results obtained indicate the existence of problems in the organization of modern vaccine prevention. The introduction of widespread restrictive and quarantine measures against the COVID-19 pandemic, on the one hand, has reduced the incidence of measles and, on the other hand, has exacerbated the difficulties in implementing measles prevention. Thus, the results indicate a possible increase in measles incidence in the population after the end of the COVID-19 pandemic.Conclusion. It is necessary to immediately develop an action plan to catch up on the coverage and increase the rate of routine vaccination, to improve the statistical record of persons subject to the introduction of the vaccine and vaccinated, as well as to overcome anti-vaccination attitude among the population.